1987
DOI: 10.2307/1058759
|View full text |Cite
|
Sign up to set email alerts
|

Municipal Management Structure and Fiscal Performance: Do City Managers Make a Difference?

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Southern Economic Association is collaborating with JSTOR to digitize, preserve and extend access to Southern Economic Journal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
107
2

Year Published

1989
1989
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(119 citation statements)
references
References 22 publications
(12 reference statements)
10
107
2
Order By: Relevance
“…10. The model used here is similar to those used by Deno and Mehay [1987] and Borcherding and Deacon [1972]. 11.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10. The model used here is similar to those used by Deno and Mehay [1987] and Borcherding and Deacon [1972]. 11.…”
Section: Resultsmentioning
confidence: 99%
“…If renters labor under greater fiscal illusion than resident homeowners, increases in POOH will be associated with lower expenditures. Deno and Mehay [1987], among others, have examined the possibility that the form taken by a city government may affect expenditures. To capture this effect, CM is a dummy variable that is equal to 1 if the city employs a city manager type of system.…”
Section: Empirical Analysismentioning
confidence: 99%
“…Since bureaucrats are themselves appointed by elected politicians, they should follow exactly the same policies as directly elected public o¢ cials, so earlier literature suggested that the method of selection of public o¢ cials has no e¤ect on policy outcomes (Baron, 1988;La¤ont, 1996). In particular, there should not be any systematic di¤erences between cities with di¤erent forms of government (Deno and Mehay, 1987). More recent literature, however, shows that the method of selection does play a role.…”
Section: Related Literaturementioning
confidence: 99%
“…Other studies conclude that reformed municipalities spend more (Sherbenou 1961;Nunn 1996;Cole 1971;French 2004). Others find a null effect (Lyons and Morgan 1977;Dye and Garcia 1978;Morgan and Pelissero 1980;Deno and Mehay 1987;Hayes and Chang 1990;Morgan and Watson 1995). 16 In states that do not officially have county governments, we use the county area, as designated by the Census of Governments.…”
Section: Methodsmentioning
confidence: 99%